2019
DOI: 10.5539/jfr.v9n1p19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boiling and Wet Frying on Nutritional and Antinutrients Content of Traditional Vegetables Commonly Consumed in Malawi

Abstract: This study was carried out to evaluate the effects of boiling and wet frying on nutritional and antinutrients content of Amaranth hybridus, Moringa oleifera, Bidens pilosa (black jack), Corchorus olitorius (Jute mallow) and Ipomea batatas (sweet potato) leaves. The edible portions of the vegetables were either boiled or wet fried for ten minutes then dried alongside the raw vegetables under the shade. Crude fats, minerals, vitamins and antinutrients were determined in the dried materials. Wet frying increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
2
0
3
Order By: Relevance
“…The leaves experienced a significantly higher reduction in the elements and anti-nutrients as a result of leaching and evaporation, especially when the leaves were pounded before boiling [23,46]. The losses of phytate due to frying and boiling might be a result of thermal degradation and dissolution in water [22]. Phytate is soluble in water and relatively heat stable during normal household boiling, but experiences higher losses in industrial processing such as canning or extrusion cooking where high temperatures are used [52].…”
Section: Levels Of Minerals and Anti-nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaves experienced a significantly higher reduction in the elements and anti-nutrients as a result of leaching and evaporation, especially when the leaves were pounded before boiling [23,46]. The losses of phytate due to frying and boiling might be a result of thermal degradation and dissolution in water [22]. Phytate is soluble in water and relatively heat stable during normal household boiling, but experiences higher losses in industrial processing such as canning or extrusion cooking where high temperatures are used [52].…”
Section: Levels Of Minerals and Anti-nutrientsmentioning
confidence: 99%
“…Montagnac [3] observed that fermentation is the most efficient processing method to remove phytate (85.6 %) from cassava roots. During frying and boiling, there are high losses of phytate, which might be a result of thermal degradation and dissolution in water [22]. On the other hand, Omosuli [23] reported no significant difference in the ash, protein, crude fiber, sodium, magnesium, calcium, and phosphorus content in raw and boiled cassava tubers.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil Penelitian ini didukung oleh penelitian lain. Diantaranya penelitian yang dilakukan Issa dkk menemukan bahwa merebus daun singkong dan daun kelor selama 10 menit dapat menurunkan kadar zink (Issa et al, 2019). Penelitian lain yang dilakukan Sharma & Sharma menemukan bahwa merebus brokoli, kubis brussel, dan bayam dengan menggunakan banyak air dapat menurunkan kadar zink dibandingkan dengan mengukus dan menggunakan microwave (Sharma & Sharma, 2022).…”
Section: Hasil Dan Pembahasan Perubahan Kadar Zink Daun Pepaya Jepang...unclassified
“…Hasil dari penelitian ini didapatkan bahwa merebus berpengaruh terhadap kadar zat besi pada tempe dan hati sapi (p<0,001) (tabel 1). Hasil dari penelitian ini diperkuat oleh penelitian lain yang menyatakan bahwa proses perebusan dapat menurunkan kandungan zat besi pada keong matah merah sebagai contoh kasus dari bahan makanan hewani, serta daun ubi, daun Moringa olifera, daun jute mallow, ubi, dan irish potato sebagai contoh kasus dari bahan makanan nabati (Purwaningsih et al, 2011;Ikanone dan Oyekan, 2014;Issa et al, 2020). Namun, terdapat perbedaan hasil penelitian dengan penelitian yang dilakukan pada rainbow trout yang menyatakan bahwa proses perebusan tidak memiliki efek signifi kan terhadap kadar zat besi (Khosroshahi et al, 2016).…”
Section: Rebusunclassified